Aplicando Sistemas Hápticos em Serious Games: um jogo para a educação em higiene bucal - Rodrigues, Herbet Ferreira (2011)
Associate to Virtual Reality, the incorporation of haptic systems makes possible to extend the level of realism and provide a more efficient way of involvement, bringing better results in performing the activities of tactile nature embedded in applications and games. However, there are few incentives for implementing these devices in serious games. The development of serious games in immersive environments and the inclusion of non-conventional devices such as haptic devices, may contribute to the motivation and learning of the player. This work has as main objective the design, study, research, development and discussion of the incorporation of haptic systems in serious games, specifically in Odontology related to adult s oral hygiene. Though, the serious games development needs a multidisciplinary team. Thus, this work also proposes and tests a serious game development process which aims to achieve a good set of approach, content and technology for a correct planning and specification of the game.